2022
DOI: 10.1021/acsomega.2c05978
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks as Potential Agents for Extraction and Delivery of Pesticides and Agrochemicals

Abstract: Pesticide contamination is a global issue, affecting nearly 44% of the global farming population, and disproportionately affecting farmers and agricultural workers in developing countries. Despite this, global pesticide usage is on the rise, with the growing demand of global food production with increasing population. Different types of porous materials, such as carbon and zeolites, have been explored for the remediation of pesticides from the environment. However, there are some limitations with these materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 158 publications
(251 reference statements)
0
10
0
Order By: Relevance
“…Even though some reviews related to MOF-based nanoplatforms in the agriculture field have been reported, in this review, we mainly focus on the progress of MOF-based nanoplatforms for crop protection, including phytopathogen, pest, and weed control and crop growth promotion, including fertilizer/plant hormone delivery (Scheme ). The principal design, mechanisms, effectiveness, and advantages of MOF-based nanoplatforms in crop protection and growth promotion are emphasized through systematically investigating the representative research work.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some reviews related to MOF-based nanoplatforms in the agriculture field have been reported, in this review, we mainly focus on the progress of MOF-based nanoplatforms for crop protection, including phytopathogen, pest, and weed control and crop growth promotion, including fertilizer/plant hormone delivery (Scheme ). The principal design, mechanisms, effectiveness, and advantages of MOF-based nanoplatforms in crop protection and growth promotion are emphasized through systematically investigating the representative research work.…”
Section: Introductionmentioning
confidence: 99%
“…Besides UCNPs, another important member of this class are MOFs. MOFs are extremely familiar due to some salient features like huge active sites on their surface, rich surface area to volume ratio, amusing topology, variety in shape and size of the pores of the materials, etc. Naturally, MOFs have been successfully envisaged in the optical detection of pesticides with the unprecedented bonus of smoothness in usage and extremely low optimum incubation time and dosage value . Unsurprisingly, MOFs have been accurately involved in monitoring food safety.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13c ] MOFs have proven to be excellent candidates for agricultural applications, particularly due to their high loading capacity, and controlled release over a longer period. [ 16,17 ] The first study using MOFs for slow release of agrochemicals was reported in 2015, for the controlled release of N and P fertilizers. [ 15c ] Demonstrating their potential application in pesticide delivery, Yaghi et al reported a controlled release of fumigant cis ‐1,3‐dichloropropene using two calcium L‐lactate MOFs, MOF‐1203, and MOF‐1201 in 2017.…”
Section: Introductionmentioning
confidence: 99%